2004
DOI: 10.1080/13550280490270798
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-4 and monocyte chemoattractant protein-1 in the neuropathogenesis of X4 simian human immunodeficiency virus infection in macaques

Abstract: Recent studies on the coreceptor usage of human immunodeficiency virus (HIV) strains associated with acquired immunodeficiency syndrome (AIDS) dementia have shown that both X4 and R5 viruses are involved in the process. The disease is associated with enhanced virus replication and monocyte chemoattractant protein (MCP)-1 production in macrophages in the brain. Using the macaque model of the disease, the authors show here that X4, macrophage-tropic simian human immunodeficiency virus (SHIV) required the enhanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It was previously shown that IL-4, favoring M2 macrophage polarization, directly activates tissue-resident macrophages to proliferate in vivo 841. Very interestingly, IL-4 was also previously shown as a biomarker for simian-human immunodeficiency virus encephalitis42434445. It is thus possible that IL-4-driven neuroinflammation is responsible for proliferation of perivascular macrophages.…”
Section: Discussionmentioning
confidence: 95%
“…It was previously shown that IL-4, favoring M2 macrophage polarization, directly activates tissue-resident macrophages to proliferate in vivo 841. Very interestingly, IL-4 was also previously shown as a biomarker for simian-human immunodeficiency virus encephalitis42434445. It is thus possible that IL-4-driven neuroinflammation is responsible for proliferation of perivascular macrophages.…”
Section: Discussionmentioning
confidence: 95%
“…CCL2 has been found in cerebrospinal fluid of infected patients (Cinque et al, 1998;Sanders et al, 1998) as well as of simian immunodeficiency virus-infected macaques (Buch et al, 2004;Zink et al, 2001). It has been identified as the elective chemoattractant factor among other chemokines for the transmigration of HIV-1infected leukocytes across the BBB (Eugenin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, baboons infected with either SHIV KU or SHIV 89.6P demonstrated productive infection of microglia (Kanmogne et al , 2002). Another study has demonstrated that the presence of IL-4 is necessary for the induction of neuropathology in X4-tropic strains of SHIV (Buch et al , 2004b). …”
Section: Shiv Infection In Macaquesmentioning
confidence: 99%